Anatomical and Cellular Requirements for the Activation and Migration of Virus-Specific CD8(+) T Cells to the Brain during Theiler's Virus Infection - Mendez-Fernandez, Yanice V. (American Society for Microbiology, 2005)
Theiler's murine encephalomyelitis virus (TMEV) infection of the brain induces a virus-specific CD8(+) T-cell response in genetically resistant mice. The peak of the immune response to the virus occurs 7 days after infection, with an immunodominant CD8(+) T-cell response against a VP2-derived capsid peptide in the context of the D(b) molecule. The process of activation of antigen-specific T cells that migrate to the brain in the TMEV model has not been defined. The site of antigenic challenge in the TMEV model is directly into the brain parenchyma, a site that is considered immune privileged. We investigated the hypothesis that antiviral CD8(+) T-cell responses are initiated in situ upon intracranial inoculation with TMEV. To determine whether a brain parenchymal antigen-presenting cell is responsible for the activation of virus-specific CD8(+) T cells, we evaluated the CD8(+) T-cell response to the VP2 peptide in bone marrow chimeras and mutant mice lacking peripheral lymphoid organs. The generation of the anti-TMEV CD8(+) T-cell response in the brain requires priming by a bone marrow-derived antigen-presenting cell and the presence of peripheral lymphoid organs. Although our results show that activation of TMEV-specific CD8(+) T cells occurs in the peripheral lymphoid compartment, they do not exclude the possibility that the immune response to TMEV is initiated by a brain-resident, bone marrow-derived, antigen-presenting cell.